Dynamical Motion Driven by Periodic Forcing on an Open Elastic Tube in Fluid (Communications in Computational Physics, 2020)
We present a three dimensional model of an open elastic tube immersed influid to understand valveless pumping mechanism. A fluid-tube interaction problemis simulated by the volume conserved immersed boundary method which prevents thegeneration of spurious velocity field near the tube and local cluster of the tube surface.In order to explain pumping phenomena without valves, average net flow is measuredby changing parameter values such as pumping frequency, compression duration, andpumping amplitude. Some frequencies that make the system reach maximal or minimal net flow are selected to study case by case. We also study the effectiveness of fluidmixing using the Shannon entropy increase rate.